Online-based sex education module to increase knowledge of LGBT sexual deviant behavior and sexual harassment among teenagers - Hana, Sarce Rien; Felle, Jessica Tirza; Camerling, Yosua Feliciano (Indonesian Research Journal in Education |IRJE|, 2025)
The research employed a quasi-experimental method by administering treatment to one group. The treatment of one of the groups was used to compare the results of the experiments. In this case, the control class is a class that is treated with expository learning, while the experimental class itself is treated with a sex education approach. The research results indicate that the provision of sex education modules is both excellent and effective, serving as a crucial first step in enhancing students' understanding of sex education, as evidenced by an increase in their knowledge. Schools, in particular, can accept the implemented modules. There is a significant difference in the average use of sex education modules for the pre-test of the experimental group (implementation of the sex education module) and the post-test of the experimental group (implementation of the sex education module). However, the significance value is greater than 0.05.